2018
DOI: 10.7554/elife.31770
|View full text |Cite
|
Sign up to set email alerts
|

Activation of G protein-coupled estrogen receptor signaling inhibits melanoma and improves response to immune checkpoint blockade

Abstract: Female sex and history of prior pregnancies are associated with favorable melanoma outcomes. Here, we show that much of the melanoma protective effect likely results from estrogen signaling through the G protein-coupled estrogen receptor (GPER) on melanocytes. Selective GPER activation in primary melanocytes and melanoma cells induced long-term changes that maintained a more differentiated cell state as defined by increased expression of well-established melanocyte differentiation antigens, increased pigment p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
111
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(132 citation statements)
references
References 39 publications
(34 reference statements)
7
111
1
Order By: Relevance
“…GPER1 has been implicated in cell proliferation in various other tumors, and its ligand was recently demonstrated to be efficacious for treatment of melanoma in mice models . Genistein activates GPER1 with an EC 50 of 133 nmol/L .…”
Section: Discussionmentioning
confidence: 99%
“…GPER1 has been implicated in cell proliferation in various other tumors, and its ligand was recently demonstrated to be efficacious for treatment of melanoma in mice models . Genistein activates GPER1 with an EC 50 of 133 nmol/L .…”
Section: Discussionmentioning
confidence: 99%
“…However, information on GPR30 or GPER in hair follicles is lacking especially in light of the well‐known beneficial effects this receptor has in inhibiting breast cancer . However, the nonclassical estrogen signaling via GPER has been reported to inhibit melanoma . In this mechanism, GPER is activated by high 17β‐estradiol levels during pregnancy that induced c‐Myc protein degradation (via PKA) that slowed tumor growth by inhibiting the immune suppressive proteins (including PD‐L1) .…”
Section: Estrogen Receptors and The Human Hair Folliclementioning
confidence: 99%
“…29 In this mechanism, GPER is activated by high 17β-estradiol levels during pregnancy that induced c-Myc protein degradation (via PKA) that slowed tumor growth by inhibiting the immune suppressive proteins (including PD-L1). 29 In general, the GPR30 or GPER cellular/molecular mechanisms also involve ERK and AKT signaling pathways that in turn influence various gene transcription elements. [27][28][29][30] Thus, much more is known about the expression and molecular (Figure 1).…”
Section: E S Trog En Recep Tor S and The Human Hair Folliclementioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that nonclassical estrogen signaling through the G protein-coupled estrogen receptor (GPER) may be tumor suppressive, including in some cancers that are not traditionally considered sex hormone responsive, such as adrenocortical carcinoma, non-small cell lung cancer, colon carcinoma, osteosarcoma, and cutaneous melanoma (4)(5)(6)(7)(8)(9). Consistent with this, we recently showed that systemic administration of a specific small molecule synthetic GPER agonist, named G-1 (10), in mice with therapy-resistant syngeneic melanoma, induced differentiation in tumor cells that inhibited proliferation and rendered tumors more responsive to αPD-1 immune-checkpoint blockade (8). GPER is expressed in many tissues (11) and signaling downstream of GPER is mediated by ubiquitous cellular proteins that mediate cAMP signaling.…”
Section: Introductionmentioning
confidence: 99%